Impact of polycyclic aromatic hydrocarbon exposure on cognitive function and neurodegeneration in humans: A systematic review and meta-analysis - Humphreys, Jessica; Valdés Hernández, Maria del C. (Frontiers in Neurology, 2023)
This review documents an emerging body of evidence concerning the neurological effect of polycyclic aromatic hydrocarbon (PAH) exposure, with regard to cognitive function and increased risk of neurodegeneration. Two electronic databases PubMed and Web of Science were systematically searched. The 37/428 studies selected included outcomes measuring cognitive function, neurobehavioral symptoms of impaired cognition, and pathologies associated with neurodegeneration from prenatal (21/37 studies), childhood (14/37 studies), and adult (8/37 studies) PAH exposure. Sufficient evidence surrounding prenatal exposure negatively impacting child intelligence, mental development, average overall development, verbal IQ, memory impairment, externalizing, internalizing, anxious, depressed behaviours, behavioural development and child attentiveness was found. Evidence concerning exposure during childhood and as an adult was scarce and highly heterogeneous, however presence of neurodegenerative biomarkers and increased concentrations of cryptic “self” antigens in serum and cerebrospinal fluid samples suggest a higher risk of neurodegenerative disease. Associations with lowered cognitive ability, and impaired attentiveness were found in children and memory disturbances, specifically auditory memory, verbal learning and general memory in adults. Although evidence is not yet conclusive and further research is needed the studies included supported the hypothesis that PAH exposure negatively impacts cognitive function and increases the risk of neurodegeneration in humans, and recommends considering the introduction of a variable “rural vs. urban” as covariate for adjusting analyses where the neurological functions affected (as result of our review) are outcome variables.